The White Dwarf Binary Pathways Survey – IV. Three close white dwarf binaries with G-type secondary stars. Issue 2 (14th December 2020) - Hernandez, M S; Schreiber, M R; Parsons, S G; Gänsicke, B T; Lagos, F; Raddi, R; Toloza, O; Tovmassian, G; Zorotovic, M; Irawati, P; Pastén, E; Rebassa-Mansergas, A; et al.
ABSTRACT: Constraints from surveys of post-common envelope binaries (PCEBs) consisting of a white dwarf plus an M-dwarf companion have led to significant progress in our understanding of the formation of close white dwarf binary stars with low-mass companions. The white dwarf binary pathways project aims at extending these previous surveys to larger secondary masses, i.e. secondary stars of spectral-type AFGK. Here, we present the discovery and observational characterization of three PCEBs with G-type secondary stars and orbital periods between 1.2 and 2.5 d. Using our own tools as well as MESA, we estimate the evolutionary history of the binary stars and predict their future. We find a large range of possible evolutionary histories for all three systems and identify no indications for differences in common envelope evolution compared to PCEBs with lower mass secondary stars. Despite their similarities in orbital period and secondary spectral type, we estimate that the future of the three systems is very different: TYC 4962-1205-1 is a progenitor of a cataclysmic variable system with an evolved donor star, TYC 4700-815-1 will run into dynamically unstable mass transfer that will cause the two stars to merge, and TYC 1380-957-1 may appear as supersoft source before becoming a rather typical cataclysmic variable star.